The species of the genus Diamesa (Diptera, Chironomidae) known to occur in Italian Alps and Apennines - Montagna, Matteo; Urbanelli, Sandra; Rossaro, Bruno (Zootaxa, 2016)
Some rare species from Italian Alps, belonging to the genus Diamesa Meigen, 1835 (Diptera, Chironomidae) are here redescribed as adult males, because only old, incomplete descriptions are available for these taxa. Terminology of male genitalia is reviewed, diagnostic features are illustrated in detail, and notes on biology and geographical distribution of the examined species are provided. An identification key to the known adult males is presented.